Cognitive-behavioral therapy for depression with older patients - Wyszomirska, Julia; Martyniak, Ewa; Krzywkowska, Karolina; Piekarska-Bugiel, Katarzyna (Pielęgniarstwo w Opiece Długoterminowej / Long-Term Care Nursing, 2020)
Symptoms of mood disorders are often ignored by the immediate surroundings. Long-term and frequent contact with the older patient enables nursing staff to establish a relationship that allows them to learn more about the patient’s well-being and life situation. Careful observation of the patient and knowledge of treatment options will not only help in making an accurate diagnosis but also in proposing appropriate forms of therapy. Depression is not a natural element of the ageing process, but a significant health problem for people at geriatric age, thus bringing suffering to both the patients and their relatives. It is empirically confirmed that the multi-factor origins of depression among the elderly require therapeutic actions, both on the biological and psycho-social level. In the paper we decided to present an overview of the research on the effectiveness of the cognitive-behavioural therapy in treatment of depression among older people. It has been assumed that not all nurses and doctors or other healthcare professionals know the basics of the cognitive – behavioural therapy. However they can potentially learn to implement a certain part of its procedures, as well as motivate patients to undertake it, because it is possible and realistic to change the way of functioning of the older adults despite of somatic disorders or cognitive deficits.